Rites of passage: Experiences of transition for forced Hazara migrants and refugees in Australia. Issue 1 (1st April 2015) - Mackenzie, Laurel; Guntarik, Olivia
This article is about resettled Afghan Hazaras in Australia, many of whom are currently undergoing a complex process of transition (from transience into a more stable position) for the first time in their lives. Despite their permanent residency status, we show how resettlement can be a challenging transitional experience. For these new migrants, we argue that developing a sense of belonging during the transition period is a critical rite of passage in the context of their political and cultural identity. A study of forced migrants such as these, moving out of one transient experience into another transitional period (albeit one that holds greater promise and permanence) poses a unique intellectual challenge. New understandings about the ongoing, unpredictable consequences of 'transience' for refugee communities is crucial as we discover what might be necessary, as social support structures, to facilitate the process of transition into a distinctly new environment. The article is based on a doctoral ethnographic study of 30 resettled Afghan Hazara living in the region of Dandenong in Melbourne, Australia. Here, we include four of these participants' reflections of transition during different phases of their resettlement. These reflections were particularly revealing of the ways in which some migrants deal with change and acquire a sense of belonging to the community. Taking a historical view, and drawing on Bourdieu's notion of symbolic social capital to highlight themes in individual experiences of belonging, we show how some new migrants adjust and learn to 'embody' their place in the new country. Symbolic social capital illuminates how people access and use resources such as social networks as tools of empowerment, reflecting how Hazara post-arrival experiences are tied to complex power relations in their everyday social interactions and in their life trajectories as people in transition. We learned that such tools can facilitate the formation of Hazara migrant identities and are closely tied to their civic community participation, English language development, and orientation in, as well as comprehension of local cultural knowledge and place. This kind of theorization allows refugee, post-refugee and recent migrant narratives to be viewed not merely as static expressions of loss, trauma or damage, but rather as individual experiences of survival, adaptation and upward mobility.